Quality evaluation of a Digital Storytelling (DST) conceptual model - Shiratuddin, Norshuhada; Tenh, Hock Kuan (2014)
Digital storytelling (DST) is an evolution of the age-old traditional storytelling, by utilizing the power of storytelling via the latest technology.In order for a digital storyteller to construct a digital story, there are sets of guided elements to be followed.However, these experts-proposed elements vary; while some are repetitive others do not cater for interactivity. Therefore, the main aim of this study is to identify the commonality of the diverse elements used by the different experts to eliminate their redundancy.A conceptual model of the identified DST core elements was constructed and reviewed by five international experts.The model was then further evaluated by 62 potential DST users. The evaluation on the quality of the model encompassed the following constructs: Perceived Ease of Understanding, Perceived Usefulness, User Satisfaction, and Perceived Semantic Quality.The findings indicated that the respondents perceived the conceptual model as having quality (mean score of 4.936 over a scale of 7.000).T-Test also revealed that there is no significant difference between the perception of those with experience in developing DST and those without experience.This suggests that the conceptual model consisting of the DST core elements, which is the main contribution of the study, could guide digital storytellers in developing digital story.